Challenges Faced by EFL Undergraduate Students in E-portfolio Writing on Google Sites - Febriana, Mita Ekda; Aridah Aridah; Weningtyas Parama Iswari (Universitas Cokroaminoto Palopo, 2025)
E-portfolios are increasingly utilized in Indonesian higher education, aligning with the